Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1111/j.1708-8305.1996.tb00696.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Travel Clinics Throughout the World

Abstract: Background: The growth of travel medicine as a specialty has been marked by a dramatic increase in the number of travel clinics worldwide. A survey was conducted of travel clinics to assess the current practice of travel medicine. Methods: A questionnaire was sent to members of the International Society of Travel Medicine, asking questions about clinic demographics, categories of advice given and immunizations available, and educational training of clinic personnel. Results: Responses from 341 clinics were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 6 publications
0
38
0
Order By: Relevance
“…New Zealand's geographic position in the Pacific make travel, tropical, migrant and wilderness medicine important 1 and inter-related, and, perhaps in contrast to other countries (Hill & Behrens, 1996), this is mostly delivered in primary health care settings (particularly in rural areas), where skill sets from practice nursing, community pharmacy and general practice all need to combine for effective delivery of care. As in the UK, there is acknowledgement of the need for primary health care professionals to achieve and maintain high standards of care (Hoveyda, McDonald, & Behrens, 2004).…”
Section: The Postgraduate Educationmentioning
confidence: 98%
“…New Zealand's geographic position in the Pacific make travel, tropical, migrant and wilderness medicine important 1 and inter-related, and, perhaps in contrast to other countries (Hill & Behrens, 1996), this is mostly delivered in primary health care settings (particularly in rural areas), where skill sets from practice nursing, community pharmacy and general practice all need to combine for effective delivery of care. As in the UK, there is acknowledgement of the need for primary health care professionals to achieve and maintain high standards of care (Hoveyda, McDonald, & Behrens, 2004).…”
Section: The Postgraduate Educationmentioning
confidence: 98%
“…same age cohort as 65% high-income country travelers), road traffic injuries (RTIs) alone are responsible for more deaths than these three diseases combined (Figure 2). 8, 10 A survey of travel medicine clinics worldwide found that 99% offered advice on infections; only 70% discussed ‘personal safety.’ 11 Fortunately, nearly two-thirds of injuries are preventable. 12, 13 Therefore, pre-travel advice regarding foreseeable dangers and how to avoid them may significantly mitigate injury risk.…”
Section: Introductionmentioning
confidence: 99%
“…This issue warrants further study. 17 Innovative methods to improve access to pretravel services for VFR travelers have used approaches such as communitybased programs (eg, in sports clubs, churches, or schools) and locallanguage programming through media to educate populations about risks. 18,19 Additional efforts to increase education and to decrease barriers to care are crucial.…”
Section: Figurementioning
confidence: 99%